Application of 9.4T MRI in Wilson Disease Model TX Mice With Quantitative Susceptibility Mapping to Assess Copper Distribution - Han, Yongsheng; Dong, Jianjian; Xu, Chenchen; Rao, Rao; Shu, Shan; Li, Guangda; Cheng, Nan; Wu, Yun; Yang, Hongyi; Han, Yongzhu; Zhong, Kai (Frontiers in Behavioral Neuroscience, 2020)
We used 9.4 tesla magnetic resonance imaging (9.4T MRI) and inductively coupled plasma mass spectrometry (ICP-MS) to investigate the distribution of copper in brain samples of a murine model of Wilson's disease (WD) following penicillamine (PCA) treatment and their correlations with the potential worsening of behavioural symptoms. Behavioural experiments showed that 7 days of PCA treatment decreased the total distance travelled in the open field and the number of rearing and climbing instances among the TX mice. Following 14 days of PCA treatment, reduced open arm ratio in the elevated plus-maze and increased escape latency in Barnes maze tests were observed. Enhanced avoidance in the open field test and movement behaviour deficits were observed after 14 days of PCA treatment. We found that PCA treatment for 21-28 days improved the cognitive abilities, exploratory behaviour, and movement behaviour of TX mice. The PCA-treated mice evinced magnetic susceptibilities in the cortex, corpus striatum, hippocampus, and amygdaloid nucleus to varying degrees across the treatment period. Low copper concentrations were found in all of the analysed brain regions of PCA-treated mice after 21-28 days (P<0.05). However, on the 7th day of PCA treatment, increased copper concentrations were observed in the primary motor cortex and cerebellum (P<0.05). After 14 days of PCA treatment, copper concentrations in the sensorimotor cortex, corpus striatum, hippocampus, and amygdaloid nucleus were higher than those detected prior to treatment. Pearson’s correlation analysis revealed a significant (P<0.05) correlation between copper concentrations and magnetic susceptibility in all of the analysed regions. Therefore, Our results indicate that copper concentration and magnetic susceptibility are associated with the alterations of mood-related behaviour, recognition memory, and movement behaviour in TX mice treated with PCA. The redistribution of copper in the TX mouse brain during PCA treatment may aggravate changes in behavioural performance. Our study demonstrates the suitability of the 9.4T MRI analysis of the brain samples of TX mice for investigating the effects of chelator therapy in patients with WD.